The Influence of Taxpayer Awareness, Tax Sanctions, Education Level, Fiscal Services and Online Tax Payment (E-Samsat) on Motor Vehicle Taxpayer Compliance in Sukabumi Regency - Eli Setiawati; Yuppy Triwidatin; Maria Magdalena Melani (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This study aims to determine the effect of taxpayer awareness, tax sanctions, education level, tax authorities and online tax payments (E-SAMSAT) on motor vehicle taxpayer compliance in Sukabumi Regency. This study uses quantitative research with survey methods. The population in this study were all motorized vehicle taxpayers who were registered at PPPD Sukabumi 1 District, Cibadak, which consisted of 369,165 taxpayers. Sampling of 100 motor vehicle taxpayers was carried out using the probability sample technique, simple random sampling method. The results showed that the influence of taxpayer awareness, tax sanctions, education level, tax authorities and online tax payments (E-SAMSAT) simultaneously had a positive effect. Partially shows that taxpayer awareness and tax sanctions have a positive effect on motor vehicle tax compliance, tax authorities services have a negative effect on motor vehicle tax compliance and for education level and online tax payment (E-SAMSAT) have no positive effect on vehicle tax compliance motorized.